Seeding a Change in Knowledge About, Attitudes Towards and Perceptions of Dating Violence in Turkish Prospective Counselors: the Effectiveness of a Train-The Prevention Program - Aracı İyiaydın, Ayşegül; Toplu Demirtaş, Ezgi; Toplu-Demirtas, Ezgi; Araci-Iyiaydin, Aysegul (Springer, 2023)
Purpose: The purpose of this study was to develop a twelve-week train-the-trainer program on dating violence (DV) prevention which we called ‘Love is Beautiful without Violence’, deliver it to prospective counselors and assess its effectiveness concerning changing their knowledge about, attitudes towards and perceptions of DV. The study was implemented in Turkey, where the prevalence of DV is quite high and college/school-based prevention programs are very limited in research. We adopted a feminist perspective for developing the program, facilitating an anti-hierarchical, egalitarian and empowering group environment. Method: In Study 1, a pre-test/post-test control group design (n = 31 for experimental; n = 39 for control) was used, and in Study 2 (n = 35), a similar pre-test/post-test group design without a control group was employed. Results: One-way ANCOVAs in Study 1 showed significant changes in counselor candidates’ post-test scores in knowledge, attitudes and perceptions between the control and experimental groups. Repeated-measures t-tests in Study 2 replicated the results, showing significant post-test changes. Conclusion: The rights-based train-the-trainer program seems to offer an effective way to approach DV prevention by rejecting hierarchies, promoting equality, empowerment and interactivity, and utilizing material and technology in its design. We highly recommend replicating it with diverse samples of prospective and in-service counselors.
Keywords: Attitudes towards dating violence; Prospective counselors; Dating violence prevention; Perceptions of dating violence; Experimental design; Counselor education; Knowledge about dating violence